Review: Effect Size Model Mastery Learning dalam Pembelajaran Kimia - Rizkiana Nurazizah; Rinaningsih Rinaningsih (Chemistry Education Review (CER), 2021)
This review article aims to identify the effect size of the mastery learning model in chemistry learning. The writing of this review article uses a meta-analysis research design using the Glass method. An effect size test was performed with a comparison of the result of 5 relevant research literature. In this study using purposive sampling technique to obtain samples. Based on the effect size test, the effect size value obtained in chemistry learning with the mastery learning model includes 1) learning outcomes of 1.32. 2) learning activities shown by the creativity of students by 4 and activities of studens by 0,48. 3) the response of students as indicated by the interest and motivation of learning students, namely 21,98 and 0,75. 4) male students have a greater effect size than female students, namely 24,53 and 22,77. Student learning outcomes can be increased by using the mastery learning model. Students have a positive response to the mastery learning model indicated by students are very enthusiastic, critical and easier to understand the material being taught.